Effects of Environmentally Relevant Ammonium Nitrate Levels Caused by Agricultural Activities on Four Amphibian Species in The Eastern Black Sea Region - Handan Karaoglu (Turkish Journal of Agriculture: Food Science and Technology)
Within the scope of this research, the chronic effects of ammonium nitrate, which is the most widely used fertilizer worldwide, on the tadpoles of Marsh Frog (Pelophylax ridibundus), the Iranian Long-Legged Frog (Rana macrocnemis), the Caucasian Parsley Frog (Pelodytes caucasicus) and the Variable Green Toad (Bufotes variabilis) were examined. To assess the chronic effects of the fertilizer, the tadpoles of all the species were exposed to 0, 5, 10, 15, 20, 25 mg/L concentrations in same conditions. The chronic concentrations were applied from the 25th developmental stage to the 42nd developmental stage. It was defined at the end of the experiments that although there were some variability between different populations of the same species or between different species in the observed effects, chronic levels of ammonium nitrate caused decreased growth rate, prolonging in time to complete metamorphosis, increased abnormalities, and mortality in general. Among the 4 amphibian species, the Variable Green Toad was the most damaged one in terms of growth reduction (on average 31-41 %), abnormality rates (on average 50-75 %), prolonged time to complete metamorphose (14-21 days on average) and mortality rates (%54-100). The most adaptive species and the least damaged one was an Iranian long-legged frog for growth reduction (on average 0-15 %), prolonged time to complete metamorphose (7-9 days on average), and mortality rates (%9-15). All the harmful effects of chronic fertilizer levels caused by agricultural activities in the region had very important for examined species in our researches and it can be said that important environmental and biodiversity problems may occur if certain precautions are not taken regarding the use of the fertilizers and if the attitudes of the farmers on this issue cannot be changed.